ANALISIS PEMINATAN PENGGUNAAN FITUR E-WALLET PADA GENERASI MILENIAL - Gishella Shafara Putri (2022)
Technology and information that are growing rapidly make changes to various fields of life, one of which is the financial sector. This is supported by the existence of a digital payment system that is easy and effective in its use called e-wallet. Almost all e-wallet users in Indonesia are mostly millennials, who are already familiar with all forms of existing technological changes. E-wallet has various features that make it easy to use it in transactions and the features provided by this e-wallet service are also diverse. This study aims to find out which e-wallet features are most in demand by the millennial generation. Judging from the number of millennials who almost all use e-wallet, of course there are features that are in great demand and used in their daily transaction activities. This research shows that the features that are in great demand by most of the millennial generation are Top-up features and Online Bill Payments and Credit Purchases. This feature is considered sufficient to meet their needs because it can provide a lot of convenience in paying bills online, buying credit and top-ups anywhere and anytime. Of course, according to the millennial generation, this feature deserves to be used in the future.